The friction of root crops on different surfaces in preparation for feeding animals. Issue 1 (January 2021) - Zazulya, A; Vedishchev, S; Filippova, O; Simonov, G; Brusenkov, A; Konovalov, V; Ilina, I
Abstract: The purpose of the research was to determine the functional dependencies of the friction parameters of root crops on various surfaces for subsequent use in energy calculations of working bodies. The research methodology provided for the experimental determination of static and kinetic friction coefficients on various surfaces and subsequent statistical processing of experimental data to obtain a regression model of indicators from the pressure of compression. Based on the research, equations were obtained that characterize the friction processes of root crops on various surfaces (steel, rubber, painted steel), which will serve for their further use in the design of machines and energy calculation. The highest friction coefficient corresponds to a pressure of 4.0-5.0 kPa, regardless of the static or dynamic loading method. At motion speeds of surfaces up to 2.0…2.6 m/s, the released juice manages to squeeze out of the contact zone. This increases the friction coefficient. At speeds from 2.000…3.095 m/s, the resulting juice does not have time to leak out of the contact zone, and therefore works as a liquid lubrication. As the speed increases, the friction coefficient decreases.